An??lise cin??tica, cinem??tica e eletromiogr??fica durante o primeiro salto do triplo hop test em mulheres com a s??ndrome da dor femoropatelar: uma compara????o com mulheres assintom??ticas - Reis, Amir Curcio dos (2013)
Patellofemoral pain syndrome (PFPS) is common in women with dynamic knee valgus and is one of the main consequences of biomechanical abnormalities in lower extremities. Kinetic, kinematic and electromyographic analysis of these patients has been widely studied during functional activities such as ascending and descending stairs, walking and running. However, these characteristics should be studied during high challenging activities, as these may lead to the occurrence of different compensatory movement patterns. The aim of the present study was to compare the biomechanical strategies of the trunk and lower limb during the transition phase between the first and second jump of the single leg triple hop test (SLTHT) in women with and without PFPS. Forty active women, aged between 18 and 35 years, were divided into two groups: patellofemoral (PFPS) and control group (CG). The volunteers performed the SLTHT and the kinetic, kinematic and electromyographic variables were collected during the transition from the first to the second hop. Eight infrared cameras, a force platform and an electromyograph were used to collect the data. The women in the PFPS group exhibited greater anterior and ipsilateral trunk lean, contralateral pelvic drop, hip adduction and internal rotation and foot pronation. They also exhibited a greater internal knee extensor moment, hip and knee abductor internal moment, less muscle activity in the gluteus medius and more biceps femoral activity during the jump cycle (P <0.05). The results demonstrate that the women with PFPS exhibited different biomechanical behavior patterns than the asymptomatic women during the single leg triple hop test.